Analysis of the KompuLearn Application to Improve Cognitive Skills According to the Growth Mindset Framework - Aisyah Nursyahidah; Enjang Ali Nurdin; Enjun Junaeti; Eka Fitrajaya Rahman; Erna Piantari (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2025)
Informatics education at the vocational high school level continues to face challenges, particularly in students' limited understanding of algorithmic and programming concepts and the prevalence of a fixed mindset. This study aims to enhance students’ cognitive skills and foster a growth mindset by integrating a growth mindset framework into the instructional design of informatics learning. The learning design incorporates the Problem-Based Learning (PBL) model and is supported by a digital mobile application called KompuLearn. The research employed a Research and Development (R&D) methodology using the ADDIE model and a one-group pretest-posttest design. The participants consisted of 30 tenth-grade students from a vocational high school. Results showed an improvement in average scores from 52.6 (pretest) to 76.2 (posttest), with a normalized gain (N-gain) of 51.1%, categorized as moderate. One-way ANOVA analysis revealed a significant difference (p < 0.001) in cognitive gains among students with different mindset tendencies. Moreover, the proportion of students exhibiting growth mindset characteristics increased, as reflected in both the data distribution across learning phases and the questionnaire responses. These findings indicate that integrating a growth mindset framework into informatics learning design—through a PBL approach and digital support—positively contributes to cognitive improvement and mindset development among vocational high school students.